State of Nature in the Perspective of Fiqh Siyasah (A Comparison Study between the Thoughts of Al-Mawardi and Thomas Hoobes) - Arake, Lukman (DIKTUM: Jurnal Syariah dan Hukum, 2023)
The concept of State of Nature is important in political theory because it helps us understand the origin of political authority and the role of government in society. The State of Nature refers to the hypothetical condition of human beings before or without political association. The analysis is about the comparison of Islamic and western views by using two figures, Al-Mawardi and Thomas Hobbes. This research aims to compare their opinion regarding the State of Nature from the perspective of Siyasah Syar’iyyah. This research uses a comparative approach and content analysis. This study discusses the critical analysis of Thomas Hobbes and Al-Mawardi's views on the concept of a state of nature. Thomas Hobbes conducted that the state of nature is the basic nature of humans who are suspicious of each other at war to find happiness or Hobbes calls it Homo humini lupus, which mean the state of the werewolf for other humans, in contrast to Al-Mawardi's view that humans are deliberately created as weak creatures so that they need interaction to help each other, humans are social creatures who need other people to survive. The research results show that Al-Mawardi and Thomas Hobbes have different views about the State of Nature. According to Al-Mawardi, humans are born in a good natural state, whereas according to Thomas Hobbes, humans are born in a bad natural state. Apart from that, Al-Mawardi argued that humans have rights that must be respected by the state, while Thomas Hobbes argued that humans must surrender their rights to the state for the sake of security and peace.